Update on the pathophysiology of rectal prolapse - Attaallah, Wafi (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Attaallah W. Update on the pathophysiology of rectal prolapse. Turk J Gastroenterol 2019; 30(12): 1074-5.